Putting together the autoimmunity puzzle - La Cava, Antonio (J Clin Invest, 2015)
Autoimmune diseases classically present with a complex etiology in which different factors concur in the generation and maintenance of autoreactive immune responses. Some mechanisms and pathways that lead to the development of imbalanced immune homeostasis and loss of self-tolerance have been identified as common to multiple autoimmune disorders. This Review series focuses on the general concepts of development and progression to pathogenic autoimmune phenotypes. A mechanistic discussion of the most recent advances in the field, together with related considerations of possible therapies, make this series of particular interest to both the basic and translational science communities.